Decompositions of Generalized Continuity in Grill Topological Spaces: Shyamapada Modak - Team, Support (Thai Journal of Mathematics, 2015)
The paper deals with some new types of generalized open set in grill topological space and its properties. Some generalized continuities will also be considered and its decompositions will be discussed.